(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: Elevated levels of plasma D-dimer increase the risk of ischemic stroke, stroke severity, and the progression of stroke status, but the association between plasma D-dimer level and functional outcome is unclear. Methods: This observational cohort type of study was done in the Department of Neurology Dhaka Medical College Hospital, Dhaka during August, 2017 to July, 2019. Total 100 patients having acute ischemic stroke were included in this study. Age > 18 year of both male & female patients with first-ever acute ischemic stroke confirmed by CT scan/ MRI who gave informed written consent including consent to give blood sample for plasma D-dimer level measurement were enrolled in this study. Results: Mean D-dimer level was 0.49±0.00 found in MRS 0, 0.57±0.19 in MRS 1, 0.49±0.00 in MRS 2, 0.70±0.33 in MRS 3, 1.46±0.77 in MRS 4, 1.60±0.59 in MRS 5 and 3.17±0.93 in MRS 6. The above findings indicate that MRS score increased with mean D-dimer significantly (p<0.05). Receiver-operator characteristic (ROC) was constructed by using D-dimer level, which gave a cut off value 1.7, with 90.9% sensitivity and 89.4% specificity for prediction of prognosis. Conclusion: Elevated plasma D-dimer level on admission was significantly associated with short-term poor outcome in patients with acute ischemic stroke. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 72-78